Metastatic Calcification Associated with Chronic Kidney Disease in a 5-Year-Old Boerboel Dog - Shakiru, Habeeb; OLA, Olawale Olawumi; Olaifa, Olanrewaju Samuel; Tijani, Monsuru Oladunjoye; Jarikre, Theophilus Aghogho; Usman, Abdulrauf Adekunle; Ajani, Tola Felicia Orotusin; Adejumobi, Olumuyiwa Abiola; Omobowale , Temidayo Olutayo (Universitas Airlangga, 2026)
Pathologic mineralization refers to the abnormal deposition of calcium salts in tissues. In dogs, metastatic calcification is an uncommon but serious complication of chronic kidney disease (CKD), resulting from disturbances in calcium/phosphorus metabolism or renal damage by infectious agents. A 5-year-old female Boerboel was presented because of one week of anorexia. Clinical assessment revealed severe emaciation, dehydration, azotemia, hyperphosphatemia, and concurrent ehrlichiosis. Despite oxytetracycline and doxycycline therapy for two days, the dog died. Necropsy and histopathological examination were performed. Grossly, there was extensive mineralization of the diaphragm, intercostal muscles, pleura, pharynx, and great vessels. Histopathology showed tubular epithelial degeneration, protein casts, tubular ectasia, and interstitial fibrosis, consistent with advanced CKD. Laboratory findings of azotemia, hyperphosphatemia, hypoalbuminemia, and hypercalcemia supported renal failure as the underlying process driving the soft tissue mineralization. Extra-renal lesions included hepatocellular atrophy with vacuolar change, Kupffer cell hyperplasia, bronchointerstitial pneumonia with pulmonary edema, and hemorrhagic follicular cystitis with mononuclear infiltration. The combined gross and histopathological findings demonstrate how renal failure-induced mineral imbalance can drive widespread soft tissue mineralization. Veterinary clinicians must monitor calcium/phosphorus status to anticipate life-threatening sequelae.